Antispasmodic Effect of Bergamot Essential Oil on Rat Isolated Gut Tissues - Laura Rombolà; Marilisa Straface; Damiana Scuteri; Tsukasa Sakurada; Shinobu Sakurada; Maria Tiziana Corasaniti; Giacinto Bagetta; Luigi Antonio Morrone (Pharmaceutics, 2022)
Preclinical data indicate that bergamot essential oil (BEO) can modulate the synaptic functions within the central nervous system (CNS). Particularly, several data shows that essential oil is endowed with reproducible analgesic and anxiolytic effects that may derived from the ability to modulate the excitatory and inhibitory neurotransmission in the CNS. Although there are differences in the functional complexity of the enteric nervous system (ENS), it is likely that the phytocomplex has biological properties in gut superimposable to those showed in the CNS. Accordingly, the aim of this study was to investigate ex-vivo the effect of bergamot essential oil and its main constituents on the contractile activity of rat isolated colon, jejunum and ileum induced by different muscle stimulants such as acetylcholine (10−6 M) and potassium chloride (80 mM). Our present data demonstrate that BEO inhibits cholinergically- and non cholinergically-mediated contractions in rat isolated gut and that linalool is the most active component. These results suggest that the phytocomplex might be useful in the treatment of spastic disorders in ENS mainly characterized by the presence of pain; incidentally, irritable bowel syndrome (IBS) is a painful condition in which a role for neurotransmitter dysfunction has been envisaged. More investigation is required for clinical translation of the present data.